First‐trimester intervention in twin reversed arterial perfusion sequence: does size matter?. (6th July 2017) - Roethlisberger, M.; Strizek, B.; Gottschalk, I.; Mallmann, M. R.; Geipel, A.; Gembruch, U.; Berg, C.
ABSTRACT: Objective: To evaluate the outcome of first‐trimester intervention (12 + 0 to 14 + 0 weeks of gestation) in pregnancies complicated by twin reversed arterial perfusion (TRAP) sequence. Methods: All monochorionic diamniotic twin pregnancies diagnosed with TRAP sequence that underwent intrafetal laser ablation (IFL) of the feeding vessels before 14 + 0 weeks of gestation at the University of Bonn between 2010 and 2015 were analyzed retrospectively for intrauterine course and outcome. Results: In the study period, 12 pregnancies with TRAP sequence were treated by IFL. Median gestational age at intervention was 13.2 (interquartile range (IQR), 12.6–13.6) weeks. In all cases, one intervention sufficed to disrupt the perfusion of the TRAP twin. There was no case of miscarriage, preterm prelabor rupture of membranes or hemorrhage. In five (41.7%) pregnancies, intrauterine death of the pump twin occurred at a median of 72.0 (IQR, 54.0–90.0; range, 48–96) h after intervention. The remaining seven pregnancies continued uneventfully resulting in birth of a healthy infant at term. A comparison of survivors and non‐survivors identified a significant difference in median discordance between crown–rump length (CRL) of the pump twin and upper pole–rump length (URL) of the TRAP twin ((CRL − URL)/CRL ratio, 0.56 vs 0.31; P  < 0.05 and URL/CRL ratio, 0.44 vs 0.68; P  < 0.05). Survivors were treated at a significantly later gestational age than were non‐survivors (median, 13.4 (IQR, 12.9–14.1) vs 12.6 (IQR, 12.5–13.1); P  < 0.05). However, none of these parameters independently predicted survival. Conclusions: Although technically feasible, IFL performed in the first trimester for TRAP sequence is associated with a significant fetal loss rate. Gestational age at intervention, (CRL − URL)/CRL ratio and URL/CRL ratio are potential predictors of pregnancy outcome. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.